The Geoeconomics and Geopolitics of Japan's 'Indo-Pacific' Strategy. (August 2019) - Scott, David
Abstract: This article seeks to trace, explain and evaluate Japan's shift towards the 'Indo-Pacific'. It argues that Japan's Indo-Pacific strategy is one that explicitly seeks to (a) expand Japan's presence across Indo-Pacific in order to (b) openly and explicitly gain greater energy security and in order to (c) tacitly and implicitly restrain China. Stephen Walt's 'balance of threat' logic is of relevance, given its focus on 'geographic proximity' and 'perceived offensive intentions' posed by China to Japan and other states in the region. The structure of the article is threefold: (a) Indo-Pacific strategic discourse in Japan, (b) Japan's Indo-Pacific actorness, with regard to its role in regional structures and its own maritime projections across the region and (c) Japan's Indo-Pacific diplomacy, with regard to the various bilateral, trilateral and quadrilateral partnerships, strategic geometry, that Japan has fashioned. The article concludes with overall evaluation of the effectiveness of Japan's Indo-Pacific strategy.